Introduction—Entering Liberty’s Refuge (Some Assembly Required) - Gregory P. Magarian (Washington University Law Review, 2012)
This brief discussion of a book I greatly admire, by an author I am fortunate to know as a colleague and a friend, cannot hope to capture all of the book’s important and interesting contributions. I will simply describe three of the book’s primary facets. Liberty’s Refuge is, first, a work of intellectual history: Inazu seeks to recover from history’s tall grass a legally respected Anglo-American tradition of assembly. The book is also a work of constitutional interpretation and legal analysis: Inazu aims to revitalize the right of assembly for our time, critiquing the legal decisions that he sees as having buried or distorted assembly and charting a path toward renewed constitutional protection for assembly. Finally, the book is a work of normative political and legal theory: Inazu’s legal analysis reflects his powerful normative commitment to the autonomy of groups—assemblies of all manner, size, and repute—that counter the state’s power and allow individuals to define themselves through engagement with others. That all sounds rosy, and in many ways, it is. But Inazu’s argument leads him into challenging and highly fraught terrain.
Keywords: " Liberty' s Refuge: The Forgotten Freedom of Assembly" John Inazu; Freedom of assembly; Right to exclude; Group rights